The Dynamics of Investment, Payout and Debt - Lambrecht, Bart M.; Myers, Stewart C. (Review of Financial Studies, 2017)
We develop a dynamic agency model of a public corporation. Managers underinvest because of risk aversion. They smooth rents and payout. They do not exploit interest tax shields fully. The interactions of investment, debt, and payout decisions can change drastically depending on managers’ preferences. Managers with power utility set investment, debt, and payout proportional to the firm’s net worth, generating a constant (possibly negative) net debt ratio. With exponential utility, investment decisions are separated from decisions about debt and payout. More profitable firms become cash cows, and less profitable firms accumulate debt, as in a pecking-order model.